IMPLEMENTASI PROFIL PELAJAR PANCASILA TEMA “GAYA HIDUP BERKELANJUTAN” SISWA KELAS IV SDN 4 SELONG - Algina Winarni Gina; Aswasulasisikin; Muh. Yazid; Doni Septu Marsa Ibrahim (STKIP Subang, 2024)
This research aims to provide further explanation about the project to strengthen the Pancasila student profile which is generally used in several state elementary schools which leads to an independent curriculum that involves elements of morals, creativity with nature and a sustainable lifestyle. The research method used in this research was qualitative research, the type of research used was descriptive qualitative. This research intended to describe and analyze the implementation of the P5 project. This research was carried out at SDN 4 Selong, the subjects of this research were class teachers and class IV students, totalling 22 students. The data sources for this research were obtained from the principal, class teacher and class IV students at SDN 4 Selong. The data collection technique used in this research was descriptive through observation, interviews and documentation and through data analysis which the researcher used in the form of data reduction, data presentation and drawing conclusions. The results of research in the implementation of the Pancasila Student Profile with the theme “Sustainable Lifestyle” for Class IV Students at SDN 4 Selong show that in implementing the P5 project there is a planning stage, an implementation stage and an evaluation stage. At the project planning stage, the level of readiness of the educational unit is at an early stage, where there are still many teachers who do not understand project-based learning well enough. The theme adopted for the even semester of the 2023/2024 academic year is a sustainable lifestyle with allocated time for project implementation every week. Furthermore, at the project implementation stage, using syntax, namely preparing learning resources such as tools and materials for the project, forming groups, and working on projects that include introduction, imagination, action or reflection project work. Moreover, at the project evaluation stage, it uses process evaluation through observation during learning activities. Based on the results of this research, several suggestions for the school system are the level of school readiness for project-based learning, for teachers, namely digging for information, taking part in training related to P5 which is carried out collaboratively and participatively, and for students to focus more on project learning so that the implementation of this project can increase students' awareness of sustainable lifestyles and Pancasila values.